মিটফোর্ড হাস্পাতাল ও ঢাকা মেডিকেল স্কুল : ইতিহাস ও ঐতিহ্য ১৮৫৮-১৯৪৭ - আহমেদ, শরীফ উদ্দিন (ঢাকা : একাডেমিক প্রেস এন্ড পাবলিশার্স লাইব্রেরি, 2007)
Articles on the history from 1858 to 1947, of Mitford Hospital and of Dhaka Medical School, both located in Dhaka, Bangladesh.
Includes bibliographical references (p. [467]-472) and index.
In Bengali; includes passages in English.
Keywords: Mitford Hospital (Dhaka, Bangladesh) -- History; Dhaka Medical School -- History; Hospitals -- Bangladesh -- Dhaka -- History; Medical colleges -- Bangladesh -- Dhaka -- History